Prevention is better than cure: a case of parents' decisions of children vaccinations / Johan Mukhlis Jan Zakri ...[et al.] - Jan Zakri, Johan Mukhlis; Rabun, Mohd Nazir; Mohamad Nazir, Mohamad Syafiqir Rahman (Universiti Teknologi MARA, Kedah, 2021)
Prevention is better than cure. Globally, it is becoming increasingly important to note that the introduction of vaccinations would help to slow down the outbreaks of infectious diseases. The purpose of this present study is to examine the level of parents' decisions of children vaccinations and measure the associations between misinformation, parents' attitudes, and knowledge with parents' decisions of children vaccination. In addition to that, this study also tends to investigate the differences in the parents' decisions of children vaccination across religious beliefs and income groups. A cross-sectional survey among parents who brought their children to the clinics was employed for this study. A quantitative method was practically used in this research and out of 250 questionnaires distributed, only 147 questionnaires were returned. Results depicted that there was a high level of parents' decisions of children vaccinations. Meanwhile, the correlations between misinformation, parents' attitudes, and knowledge were found to be significantly correlated with the parents' decisions of children vaccination. Besides that, results also illustrated that there was a significant difference in the parents' decisions of children vaccination across religious beliefs, but no significant difference in the parents' decisions of children vaccination across income group. Thus, this study had contributed to providing valuable information among the parents as well as achieving a greater understanding of the level of parents' decisions of children vaccination. The government should portray its vital role in promoting better health care of children vaccination through the enhancement of programmes and campaigns.